Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.33448/rsd-v10i10.18318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between growth performance in two silvopastoral systems comprising trees, short-lived perennial shrub, a forage, and livestock)

Abstract: We aim to determine the growth performance of two 20-year-old silvopastoral systems comprising two timber trees, a palm tree), a short-lived perennial shrub, a forage and livestock; and to investigate fibre features and certain physical and mechanical properties of two timber trees (Myracrodruon urundeuva and Peltophorum dubium) in two plantation systems. The first system is called MP with two timber trees and the second one is called MPS with two timbers and a palm tree. The studied systems showed that it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…In another study on agrosilvi-pastoral systems using the species Myracrodruon urundeuva and Peltophorum dubium, it was found that this system can be used successfully, as they produce wood with greater mechanical resistance and better quality for energy (Longui et al 2021). In a study with Tectona grandis wood from an agrosilvi-pastoral system, it was found that when compared with literature results referring to homogeneous plantations, teak wood from an agrosilvi-pastoral system maintained its technological qualities in terms of basic density, the which is a favorable option for the use of this species in the format of associated plantations (Oliveira et al 2020).…”
Section: Wood Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study on agrosilvi-pastoral systems using the species Myracrodruon urundeuva and Peltophorum dubium, it was found that this system can be used successfully, as they produce wood with greater mechanical resistance and better quality for energy (Longui et al 2021). In a study with Tectona grandis wood from an agrosilvi-pastoral system, it was found that when compared with literature results referring to homogeneous plantations, teak wood from an agrosilvi-pastoral system maintained its technological qualities in terms of basic density, the which is a favorable option for the use of this species in the format of associated plantations (Oliveira et al 2020).…”
Section: Wood Propertiesmentioning
confidence: 99%
“…In summary, agrossilvipastoril systems have shown to be promising in several aspects, being possible to successfully combine fast-growing shrub species, resistant grasses consumed by animals and tree species that can produce different products with a cycle of more than 50 years, for example, ornamental plants, hearts of palm, landscaping, fruits, seeds, bee pasture and wood with different properties (Longui et al 2021).…”
Section: Wood Propertiesmentioning
confidence: 99%
“…(KLEIN et al, 2017; PORTELA, SILVA e PINÃ-RODRIGUES, 2001), em plantios comerciais a pleno sol(HEID et al, 2016), integrada a sistemas agroflorestais(LONGUI et al, 2021), não foram encontrados trabalhos de médio e longo prazo para a espécie, sob diferentes condições de A partir dos resultados observados pela presente pesquisa, as recomendações técnicas para o plantio de P. dubium com fins comerciais podem ser aperfeiçoadas. Visto que, o…”
unclassified